Analysis Of Service Quality And Healthy Food Healthy Food Product Quality Towards Customer Satisfaction At Ayam Keprabon Gading Serpong Restaurant - Yanah, Ani; Tanu, Barbie Valerina; Natalie, Lytiana (International Journal of Health, Medicine, and Sports, 2025)
This study aims to analyze the impact of service quality and healthy food product quality on customer satisfaction at Ayam Keprabon Restaurant, Gading Serpong. Using a qualitative approach, data were collected through observations and interviews with four customers of the restaurant. The findings indicate that high-quality products and excellent service significantly influence customer satisfaction.